Helminth species dependent effects on Th1 and Th17 cytokines in active tuberculosis patients and healthy community controls. - Gezahegn Bewket; Amare Kiflie; Fitsumbrhan Tajebe; Ebba Abate; Thomas Schön; Robert Blomgran (Public Library of Science (PLoS), 2022)
Despite that the impact of different helminth species is not well explored, the current dogma states that helminths affect the Th1/Th2 balance which in turn affects the risk of tuberculosis (TB) reactivation and severity of disease. We investigated the influence of helminth species on cytokine profiles including IL-17A in TB patients and healthy community controls (CCs). In total, 104 newly diagnosed pulmonary TB patients and 70 HIV negative and QuantiFERON negative CCs in Gondar, Ethiopia were included following helminth screening by stool microscopy. Plasma samples and ex vivo stimulation of peripheral blood mononuclear cells (PBMCs) with purified protein derivative (PPD) and Staphylococcus enterotoxin B (SEB) was used to determine cytokine profiles by cytometric bead array. In CCs, Ascaris lumbricoides or Schistosoma mansoni infections were associated with an impaired Th1-type response (IFN-gamma, IL-6 and TNF-alpha) in PBMCs mainly with SEB stimulations, whereas in TB patients only hookworm infection showed a similar pattern. Among CCs, the IL-17A response in PBMCs stimulated with SEB was higher only for S. mansoni, whereas in TB patients, the elevated systemic IL-17A plasma level was significantly suppressed in hookworm infected TB patients compared to patients without helminth coinfection. Following treatment of TB and helminth infection there was a general decrease in ex vivio IL-10 and TNF-alpha production in unstimulated, PPD or SEB stimulated PBMCs that was the most pronounced and significant in TB patients infected with S. mansoni, whereas the follow-up levels of IFN-gamma and IL-17A was significantly increased only in TB patients without helminth coinfection from PBMCs stimulated mainly with SEB. In summary, in addition to confirming helminth specific effects on the Th1/Th2 response before and after TB treatment, our novel finding is that IL-17A was impaired in helminth infected TB patients especially for hookworm, indicating a helminth species-specific immunoregulatory effect on IL-17A which needs to be further investigated.